The Rise of American Minimum Wages, 1912-1968 - Price Fishback; Andrew Seltzer (Institute of Labor Economics (IZA), 2020)
Minimum wages have been among the most controversial government interventions in labor markets. There have been several waves of minimum wage activity over the past century, beginning with a 1912 Massachusetts law. Since 1938 minimum wages in the United States have been set by a complex array of federal and state laws, with state laws sometimes exceeding the national law and closing important coverage gaps. Between 1938 and 1968, the real value of the federal minimum wage was generally increasing. Coverage gaps continued to be closed by amendments to federal legislation into the 1970s. In the 1980s, the real minimum rate declined sharply, and has since this time never again reached the level of 1955-1980. In this paper we examine the political economy of early minimum wage laws, focussing on the role of interest groups, politicians, courts, economists, and the general public.
Keywords: N32; N42; J88; 330; minimum wages; political economy